2014
DOI: 10.1007/s13524-014-0345-2
|View full text |Cite
|
Sign up to set email alerts
|

Why Lifespans Are More Variable Among Blacks Than Among Whites in the United States

Abstract: Lifespans are both shorter and more variable for blacks than for whites in the United States. Because their lifespans are more variable, there is greater inequality in length of life—and thus greater uncertainty about the future—among blacks. This study is the first to decompose the black-white difference in lifespan variability in America. Are lifespans more variable for blacks because they are more likely to die of causes that disproportionately strike the young and middle-aged, or because age at death varie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
32
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 42 publications
(37 citation statements)
references
References 31 publications
4
32
0
Order By: Relevance
“…In addition to presenting total cause-specific spread, allocation, timing, and joint effects, we also present effects separately by sex. Edwards and Tuljapurkar (2005) and Nau and Firebaugh (2012) found similar variability patterns for women and men, whereas Firebaugh et al (2014) found that effects (particularly for spread) are larger for women than for men.…”
Section: Methodsmentioning
confidence: 79%
See 2 more Smart Citations
“…In addition to presenting total cause-specific spread, allocation, timing, and joint effects, we also present effects separately by sex. Edwards and Tuljapurkar (2005) and Nau and Firebaugh (2012) found similar variability patterns for women and men, whereas Firebaugh et al (2014) found that effects (particularly for spread) are larger for women than for men.…”
Section: Methodsmentioning
confidence: 79%
“…The decomposition process is developed and described in detail elsewhere (Nau and Firebaugh 2012; see also Firebaugh et al 2014). Briefly, this methodology decomposes differences in lifespan variance between two populations into the contributions of differences in (1) cause-specific variability in age at death (spread effect), (2) number of deaths attributable to each cause (allocation effect), and (3) variability in cause-specific mean age at death (timing effect).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, cause-specific contributions to variance have only recently been explored. A study of the difference between blacks and whites found that causes of death contributing the most to differences in V were distinct from causes contributing most to the difference in e 0 (15). In particular, whereas previous work showed that about one-half the gap in e 0 was because of differences in CVD, cancer, and diabetesrelated mortality (16), the gap in V was largely because of accidents, violence, and HIV/AIDS.…”
mentioning
confidence: 94%
“…Also, do causes that contribute substantially to increase in e 0 also contribute in a major way to declines in V? The work by Firebaugh et al (15) shows that this need not be true.…”
mentioning
confidence: 99%